Fracture Analysis on Flexspline and Flexible Bearing of the Harmonic Reducer - Mu Xiaobiao; Shao Zhuhao; Hao Chunhui; Gao Mingyan; Zhang Chaolei (Jixie chuandong)
Microstructure and mechanical properties of the failure flexspline and the Japanese flexspline for harmonic reducers and fracture reason are analyzed by quantitative of microstructure, determination of mechanical properties and fracture analysis. The result shows that the microstructure of the flexspline of the failed harmonic reducer is the same as that of Japan, both of which are tempered troostite. The average grain size of the failure flexspline is 8.2 μm, which is 1.5 μm higher than that of the Japanese flexspline. The microstructure of the failure and Japanese flexible bearings is tempered martensite. The average grain size of failure flexible bearings is 13.1 μm, which is 6.9 μm higher than that of the Japanese flexible bearings. The fracture morphology of the flexspline presents brittle fracture characteristics without obvious crack source. The fracture of flexible bearings shows obvious fracture trend. There are obvious crack trends in the fracture of flexible bearing. The crack source is pinpointed at the region where large agglomerative inclusions are observed. The poor purity of flexible bearing and the coarse microstructure with poor ability to hinder crack propagation are the main causes of premature failures of domestic harmonic reducers.